Tangerang City Government Collaboration in Household B3-Specific Waste Management - Marlinda Erfanti; Mustika Berliantoro; Imammujahid Al Amin (Journal of Public Administration and Government, 2023)
The research aims to provide an overall picture that explains the collaborative process of the Tangerang City government in the management of household B3-specific waste. In addition to inorganic and organic waste, there are other types of waste generated from households, namely waste containing Toxic and Hazardous Materials (B3). However, in Tangerang City, there are not many people who do segregation for this specific type of B3 waste. Household specific B3 waste has been regulated in Government Regulation No. 81 of 2012 which regulates the Management of Household Waste and Household-like Waste and PP No. 27 of 2020 which regulates the management of Specific Waste which is far more diverse and complex. Included in specific types of B3 household waste include hair spray, air freshener, clothes bleach, insect repellent, bathroom cleaners, electronic goods, etc. Garbage that is mixed and contains hazardous substances will seep into the earth and become a cause of environmental pollution. Meanwhile, harmful substances in the form of gases will be released into the air and cause depletion of the ozone layer. For the management of specific B3 waste, households need separate methods that require a lot of money. As a solutive step for household-specific B3 waste management, the Tangerang City Government is collaborating with the private sector to address household-specific B3 waste management problems in Tangerang City. This research uses qualitative research methods and in-depth interviews, observation, and documentation as well as data analysis using the concept of collaborative governance by Ansell and Gash (2008) with an emphasis on process aspects in collaborative government governance. From the results of the analysis that has been carried out in this study, this form of collaboration in the management of B3-specific waste is not optimal. There are several recommendations that are concluded for optimizing collaboration in the future.